Media Framing of Religious Minorities in Greece: The Case of the Protestants - Bantimaroudis, Philemon (Journal of media and religion, 2007)
During the past 50 years, Greece has demonstrated significant progress on different social, economic, and political fronts. After joining the European Union in 1981, Greece received generous funding to engage in a radical reformation of its public services and the industrial and agricultural sectors. The central objective of different Greek governments has been an overall convergence of the Greek standards of living with the European standards of living. Thus far, Greece has only partially succeeded in this goal. In the context of civil liberties and human rights, Greece has improved its performance. In sharp contrast to the 1960s, Greek citizens are no longer persecuted because of their political beliefs or party affiliations. All political views from the far right to the far left are tolerated and represented in the Greek Parliament. However, despite Greece's progress in protecting and respecting political views, similar progress has not been marked in the context of religious beliefs. Its noticeable failure to separate Church and State and the obtrusive influence of the Church of Greece on governmental affairs has prevented the country from functioning like its western counterparts (Agouridis, 1998, 158). Various institutions are involved in the sensitive area of religious expression. First, the Greek Orthodox Church, 1 also known as the Church of Greece, which the Greek Constitution recognizes as the "prevailing" religion, undoubtedly remains a significant element of national/cultural identity, because of its cultural past, as well as a powerful political force claiming a role in the political affairs of the country, both internal and external. Also, the Greek Government's Ministry of Education and Religious Affairs oversees all activities related to public religious education, and supervises all non-Orthodox religious entities (Stathopoulos in Christopoulos, 1999). 1The terms Greek Orthodox Church and Church of Greece are used interchangeably. The same applies for the terms Greek Protestants and Greek Evangelicals.